Relations between the Scandinavian-Baltic region states and Ukraine: military-political and economic dimensions - V. V. Vorotnikov (Международная аналитика)
The article is devoted to the relations of the Scandinavian-Baltic region states (Denmark, Estonia, Finland, Latvia, Lithuania, Norway, Sweden) and Ukraine in the military-political and economic spheres. These countries had engaged in Ukrainian affairs long before 2013−2014. This happened soon after «the Orange Revolution» and, then, the trend became more pronounced during the implementation of the program «Eastern Partnership». The most active actors on the Ukrainian track in their subregions are Sweden (until 2014 — one of the largest investors in its economy) and Lithuania, which in 2015 started to supply lethal weapons to Ukraine. The countries of the Scandinavian-Baltic region provide financial assistance to Ukraine which is symbolic compared to development aid, but considerable for Ukrainian economy. Financing is traditionally directed to promotion of effective public administration, democracy, human rights (including gender equality), systemic economic reforms, sustainable development (including energy efficiency), etc. From a strategic perspective, military cooperation of the Scandinavian-Baltic region countries with Ukraine is nominal as well. Against this background, completely divergent assessment of the situation in Ukraine continues to be the most important stumbling block in the relations between Russia and the states of the region. This does not give any grounds for early softening of their value-based foreign policy towards Russia.